The reciprocal relationship between gait and handgrip strength across different age groups - Hyeon, Gayeong; Kim, Changhun; Shin, Sunghoon (Frontiers in Public Health, 2025)
IntroductionThis study aimed to investigate the reciprocal relationship between grip strength and gait function across different age groups to better understand age-specific physical performance patterns.MethodsA total of 328 participants were categorized into young (19–39 years), middle-aged (40–59 years), and older adults (60–89 years). Grip strength, spatiotemporal gait parameters, and gait variability were assessed using validated measurement tools. To investigate the reciprocal relationship, hierarchical moderated regression analyses were conducted to assess the effects of grip strength on spatiotemporal gait parameters, considering age as a moderator, whereas stepwise linear regression analyses were performed to evaluate the predictive effects of spatiotemporal gait parameters on grip strength, controlling for age and additional covariates.ResultsGrip strength significantly influenced gait performance variables—stride length, step length, and walking speed—with the strongest effects observed in older adults. However, grip strength did not significantly impact gait variability, which appeared to be primarily affected by age-related neuromuscular changes. Furthermore, this study highlights that gait performance itself may influence grip strength, particularly in older adults, suggesting a reciprocal relationship between upper and lower limb function. Specifically, the proportion of the double support phase—known to increase with age—was found to be a significant predictor of grip strength, likely reflecting compensatory adaptations for balance maintenance under conditions of declining neuromuscular function.DiscussionThese findings suggest that the mechanisms underlying gait performance differ from those related to gait stability. While grip strength may serve as an accessible biomarker for functional ability in older adults, its relevance in younger and middle-aged adults appears limited. Age-specific interventions are recommended: for older adults, grip-strengthening exercises combined with gait stability training may be beneficial; for younger and middle-aged adults, enhancing neuromuscular coordination and flexibility could be more effective in supporting gait function.